Cystic fibrosis disease severity correlates with plasma levels of desmosine and isodesmosine, biomarkers of elastin degradation. Issue 2 (17th June 2019) - Ma, Shuren; Geraghty, Patrick; Dabo, Abdoulaye; McCarthy, Cormac; McElvaney, N. Gerry; Turino, Gerard M.
Monitoring the integrity of the lungs using biomarkers is a major goal as an indicator for patient prognosis, especially in diseases like cystic fibrosis (CF) where 85% of mortality is a result of lung disease [1]. Advances in the precision of current biomarkers and identification of new biomarkers are needed to accelerate CF drug development. The development of biomarkers to reflect disease progression or the effect of new therapy has the potential to improve patient care and new drug discovery. Systemic monitoring of biomarkers via body fluids such as blood sampling is ideal as a relatively noninvasive approach to monitor patient disease progression. Blood can easily be obtained from patients of all ages despite lung disease severity. An ideal biomarker for CF disease progression would allow diagnosis of patients following an exacerbation and monitor changes in response to treatment [2]. The airways of CF patients have a large population of neutrophils that are associated with the lung inflammation and tissue remodelling observed with the disease [3]. The abundance of neutrophils and their intracellular components, such as neutrophil elastase [4], alter the lung microenvironment for example the extracellular matrix proteins, which represent plausible targets for biomarkers. The unique elastin degradation products desmosine and isodesmosine (DI) are stable cross-linking amino-acids that are detectable in body fluids as indicators of lung damage [5], and are proposed as biomarkers for lung disease severity. Elastin degradation is reported to be increased in patients with CF [6], with elevated DI levels observed in the urine of CF patients. However, as DI is present at extremely low concentrations in body fluids, their precise and specific measurement has been a challenge and until recently were not envisioned as a viable biomarker. Using a quantitative ion mobility-mass spectrometry (MS) method to analyse free DI, DI concentrations are consistently detected and are enhanced in the urine of chronic obstructive pulmonary disease (COPD) patients relative to healthy controls [7]. The increased sensitivity in the method of analysis of DI increases specificity and sensitivity for DI measurements in body fluids, including plasma, sputum, bronchoalveolar lavage fluid and urine [8, 9]. The liquid chromatography–tandem mass spectrometry (LC–MS/MS) method can avoid homologous interference of both desmosine and isodesmosine. When detecting DI by ultraviolet or ELISA, DI levels detected in plasma are higher and have more signal-to-noise than the LC–MS/MS method. Here, we investigate plasma samples from CF patients for DI levels and determined whether DI levels in plasma correlates with pulmonary function and the frequency of annual exacerbations. Novel methodological approaches now demonstrate that the unique elastin degradation products desmosine and isodesmosine are detectable in plasma of cystic fibrosis patients and correlate to lung function, exacerbation frequency and disease progression http://bit.ly/2VwZOcx